Analysis of Ethnopharmaceutical Studies of Traditional Medicine for the Management of Jaundice Due to Hepatic Disorders by the Mandar Tribe of West Sulawesi, Indonesia - Sari, Dewi Weni; Kharisma Jayak Pratama; Annora Rizky Amalia (HM Publisher, 2024)
Jaundice, or icterus, is a medical condition characterized by yellowing of the skin and whites of the eyes. This is caused by a buildup of bilirubin in the blood, which is a waste product of the breakdown of red blood cells. Liver disorders, such as hepatitis, are the most common cause of jaundice. The Mandar tribe in West Sulawesi Indonesia has a traditional healing tradition that has been passed down from generation to generation. This traditional medicine is often used to treat various diseases, including jaundice. This study aims to analyze the ethnopharmaceutical traditional treatment for jaundice in the Mandar tribe in West Sulawesi. This research used a descriptive observational method with traditional healthcare respondents. Data was collected through interviews and observations of traditional healers and patients who used traditional medicine. The data was analyzed descriptively to determine the type of plant, part of the plant used, processing methods, and how traditional medicines are used. This research found 14 plant species from 13 families that were used as medicine for jaundice. Two types of plants are typically used by the Mandar tribe, namely lapo-lapo (Melanolepis multiglandulosa) and barorang (Blumea balsamifera). The parts of the plant most commonly used as medicine are leaves (43%), followed by fruit (29%), stems (14%), roots (7%), rhizomes (4%), and herbs (3%). Plant processing by pressing and boiling is the most widely used (50% each). The most common method of use is boiling (70%), followed by pounding (20%) and eating directly (10%). This research found 14 plant species from 13 families that were used by the Mandar tribe as medicine for jaundice. Two types of plants are typically used, namely lapo-lapo and barorang. This research provides important information about the Mandar tribe's ethnopharmacology for jaundice and can be a basis for the development of more effective and safer traditional medicines.